Size effect on flexural behavior of ultra-high-performance concrete beams with different reinforcement. (July 2022) - Cao, Xia; Ren, Yi-Cheng; Qian, Kai; Fu, Feng; Deng, Xiao-Fang; Zhang, Wei-Jia
Abstract: In this paper, in order to investigate the size effect on the flexural behavior of ultra-high-performance concrete (UHPC) beams, two groups UHPC beams with sizes of, 150mm × 250mm × 2300mm (small) and 300mm × 500mm × 4600mm (large), were tested through four-point bending test. Each group consists of four UHPC beams with different rebar type and reinforcement ratio. The experimental results showed that the flexural strength, normalized deflection, and fracture toughness of HRB400 steel reinforced UHPC beams was not affected by size effect. The normalized deflection at ultimate bearing capacity of GFRP reinforced UHPC beams is affected by size effect, but no size effect was shown for whole deflection process. The flexural strength and fracture toughness of GFRP reinforced UHPC beams changed from having size effect to no size effect with the increase of reinforcement ratio. Furthermore, the maximum crack width, number of cracks and average crack spacing of both UHPC beams were sensitive to the size of specimen, while no significant size effect was shown for ductility of both UHPC beams.